Using Ultrasonic Technique to Measure Some Petrophysical Properties of Yamama Formation at Ratawi-7 Oil Well Core Samples, Southern Iraq - Khorshid, Salman; Salman, Rassoull (Iraqi Journal of Science, 2023)
Twenty nine core samples were taken from Ratawi 7 Oil well according to the presence of oil in formation and availability of core samples. This well is located in the province of Basra/southern Iraq. The samples were collected from Yamama Formation. The core samples are taken from the well at different depths, ranging between (3663m-3676m). The range of Vp for these core samples is (668-4017 m/sec) and its average is (1779 m/sec), While the range of Vs is (291-1854 m/sec) and its average is (796 m/sec). In the current study the ultrasonic method is conducted to measure Vp, Vs as well as some petrophysical properties for core samples and some elastic moduli such as (Young's modulus, Bulk modulus, Shear modulus, Poisson's ratio and Lame's constant) depending on the values of Vp and Vs as well as to density. The relationship between seismic wave velocities and elastic moduli and petrophysical properties are plotted. The average of densities for this well is (2661 kg/m3). The average of porosities which calculated depending on Vs values for this well is (22.08%). Two core samples from Rt7c1 well are selected to conduct laboratory measurements for porosity and compare it with the results of porosity which calculated from Vs, the results show that the values of porosities are similar as shown in the following table: